Pengembangan Sensor Antioksidan berbasis Kertas Zonamikro dengan Imobilisasi DPPH pada Sampel Ekstrak Tanaman - Muhammad Fantoni; Indah Yulia Ningsih; Moch. Amrun Hidayat; Bambang Kuswandi (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Development of a paper-based antioxidant sensor using DPPH reagent. This sensor is made using a screen-printing method to create a 5 mm diameter detection zone which is immobilized with DPPH reagents. The analysis was carried out in one step by immobilizing antioxidants/samples in the detection zone. After reduction by antioxidants, DPPH radicals become stable DPPH molecules, resulting in a change in color from purple to pale yellow. The purple intensity of DPPH was inversely proportional to the antioxidant activity of the sample and was measured using the help of ImageJ software. The optimal conditions for using DPPH reagents at a concentration of 5 mM and the volume in each detection zone were 3 µL. Characterization of this sensor analysis was carried out on gallic acid with the response time in the 12-minute, linearity with r = 0,9895, detection limit (LOD) value 0,0349 mM GAE, the quantitation limit (LOQ) value was 0,1164 mM GAE, with precision <2% (RSD), and meets the accuracy range of 97-103%. This sensor is then validated against DPPH spectrophotometry UV-Vis by analyzing antioxidant activity from plant extracts. The results showed no significant differences for the gallic acid equivalent for all samples obtained from the two methods at a confidence level of 97-103%, indicating that the method developed could be relied upon to analyze antioxidant activity from real samples. Finally, the paper-based antioxidant sensor is known to be stable for three days when stored in the refrigerator (2- 4 °C), stable for 2 hours at room temperature (25ºC), and makes paper sensors easy to use for end users.